Non-Carrier Nanoparticles Adjuvant Modular Protein Vaccine in a Particle-Dependent Manner - Seth, Arjun (PLoS One, 2015)
Nanoparticles are increasingly used to adjuvant vaccine formulations due to their biocompatibility, ease of manufacture and the opportunity to tailor their size, shape, and physicochemical properties. The efficacy of similarly-sized silica (Si-OH), poly (D,L-lactic-co-glycolic acid) (PLGA) and poly caprolactone (PCL) nanoparticles (nps) to adjuvant recombinant capsomere presenting antigenic M2e modular peptide from Influenza A virus (CapM2e) was investigated in vivo. Formulation of CapM2e with Si-OH or PLGA nps significantly boosted the immunogenicity of modular capsomeres, even though CapM2e was not actively attached to the nanoparticles prior to injection (i.e., formulation was by simple mixing). In contrast, PCL nps showed no significant adjuvant effect using this simple-mixing approach. The immune response induced by CapM2e alone or formulated with nps was antibody-biased with very high antigen-specific antibody titer and less than 20 cells per million splenocytes secreting interferon gamma. Modification of silica nanoparticle surface properties through amine functionalization and pegylation did not lead to significant changes in immune response. This study confirms that simple mixing-based formulation can lead to effective adjuvanting of antigenic protein, though with antibody titer dependent on nanoparticle physicochemical properties.